2001
DOI: 10.1038/sj.ejhg.5200679
|View full text |Cite
|
Sign up to set email alerts
|

A 31 bp VNTR in the cystathionine β-synthase (CBS) gene is associated with reduced CBS activity and elevated post-load homocysteine levels

Abstract: Molecular defects in genes encoding enzymes involved in homocysteine metabolism may account for mild hyperhomocysteinaemia, an independent and graded risk factor for cardiovascular disease (CVD). Although heterozygosity for cystathionine b-synthase (CBS) deficiency has been excluded as a major genetic cause of mild hyperhomocysteinaemia in vascular disease, mutations in (non-)coding DNA sequences may lead to a mildly decreased CBS expression and, consequently, to elevated plasma homocysteine levels. We assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 32 publications
5
53
0
1
Order By: Relevance
“…In the present study, we observed six different alleles, of which alleles 16 to 21 showed similar allele frequencies compared with those in our previous report of a Dutch population 7 and those of earlier reports. 8,19 Allele 15 was not reported before, probably because its frequency is rather low.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…In the present study, we observed six different alleles, of which alleles 16 to 21 showed similar allele frequencies compared with those in our previous report of a Dutch population 7 and those of earlier reports. 8,19 Allele 15 was not reported before, probably because its frequency is rather low.…”
Section: Discussionsupporting
confidence: 75%
“…However, we observed that this most common allele in fact consist of 18 repeat units, resulting in a different numbering in which our allele 18 is the most common. 7 They reported that the genotypes 17 -18 and 18 -19 had lower delta (ie increase upon methionine loading) tHcy concentrations that the most common 18 -18 genotype, and that this observation is probably caused by linkage disequilibrium with upstream transcriptional regulatory elements. They argued that the occurrence of alternative splicing is prevented by a G to A substitution at the exon -intron border of the second repeat unit.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations